1993
DOI: 10.1016/0140-6736(93)91223-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rates in displaced and resident populations of central Somalia during 1992 famine

Abstract: Famine and civil war have resulted in high mortality rates and large population displacements in Somalia. To assess mortality rates and risk factors for mortality, we carried out surveys in the central Somali towns of Afgoi and Baidoa in November and December, 1992. In Baidoa we surveyed displaced persons living in camps; the average daily crude mortality rate was 16.8 (95% CI 14.6-19.1) per 10,000 population during the 232 days before the survey. An estimated 74% of children under 5 years living in displaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…3,4 Over several months of the 1992 famine in Somalia, 74% of children younger than 5 years in displaced persons camps were estimated to have died. 7 Among Rwandan and Burundian refugees in the Democratic Republic of the Congo in 1996, 54% of all deaths were among children under 5 years. 8 In some settings, mortality rates of older children and adults are comparable to or exceed those of young children; this is more probable after outbreaks of cholera or dysentery, or when armed conflict results in many civilian casualties.…”
Section: Child Morbidity and Mortality In Complex Emergencies Overviewmentioning
confidence: 99%
“…3,4 Over several months of the 1992 famine in Somalia, 74% of children younger than 5 years in displaced persons camps were estimated to have died. 7 Among Rwandan and Burundian refugees in the Democratic Republic of the Congo in 1996, 54% of all deaths were among children under 5 years. 8 In some settings, mortality rates of older children and adults are comparable to or exceed those of young children; this is more probable after outbreaks of cholera or dysentery, or when armed conflict results in many civilian casualties.…”
Section: Child Morbidity and Mortality In Complex Emergencies Overviewmentioning
confidence: 99%
“…In Somalia, death rates of internally displaced persons ranged from 2-to-5 times greater than the baseline death rates of Somali people (Moore et al, 1993). Among internally displaced populations, the risk of premature death is more difficult to quantify as the environment is often so volatile that surveys are impossible to conduct.…”
Section: Economic and Related Variablesmentioning
confidence: 99%
“…The immediate displacement phase is typically characterized by extremely high malnutrition. In the Sudan, malnutrition rates exceeded 60%, while even higher rates were recorded in Somalia, as much as 80% (Moore et al, 1993). Additionally, many studies of civilian refugee populations in settlement camps have observed extremely poor sanitary conditions as well as significant crowding, which in turn increases the risk of disease transmission (Ahoua et al, 2006).…”
Section: Economic and Related Variablesmentioning
confidence: 99%
“…For example, as many as one in seven of those who died in the Irish famine of the 1840s were recorded as having died not of food shortage ('starvation'), but of diarrhoeal diseases, including dysentery (Kennedy et al 1999). 8 Similarly, diarrhoeal diseases were the prime cause of mortality in Somalia during the 1991/2 famine, Afghanistan during 2001, and in the Democratic Republic of Congo from 1999 to 2002 (Moore et al 1993;Assefa et al 2001;Salama et al 2004). …”
Section: Zinc (Diarrhoeal Disease Pneumonia Malaria)mentioning
confidence: 99%